Integrating the SDGs into Corporate Strategy: A Case Study of EDP Group - Helena Costa Oliveira; Marta Gomes; Isabel Maldonado; Susana Bastos; Paulino Silva (Administrative Sciences)
This research investigates the integration of the Sustainable Development Goals (SDGs) into the business practices of the Portuguese energy giant EDP Group. We analyse the company’s annual reports, sustainability reports, and public statements to explore the motivations, challenges, and key organisational dimensions involved in this process. Our findings reveal that EDP Group’s strong commitment to sustainability, external pressures, and stakeholder expectations have driven the integration of the SDGs into its strategic and operational plans. The company’s cultural emphasis on environmental and social responsibility and formal management control systems has facilitated this integration. However, challenges such as the lack of standardised metrics to measure social and environmental impacts and the evolving regulatory landscape hinder progress. This study contributes to understanding how large corporations can effectively integrate the SDGs into their business models, providing valuable insights for practitioners and policymakers.